A estrutura do sistema do direito do trabalho em uma sociedade mundial além da OIT: OMC e organizações sindicais internacionais - Silva, Lenara Giron da (Universidade do Vale do Rio dos Sinos, 2015)
When speaking generally, about globalization, many challenging issues arise, many involving the Law’s focus of interest. Presently, the exasperations of the economic system cannot ignore the Labor Law, which has been deeply affected by the effects and requirements of this worldwide phenomenon. This paper aims to analyze how the transactional labor rights are being regulated in the global society. Labor relations are increasingly widespread and without parameters, due to the constant pursuit of profit by multinational companies that are organized in seeking low production cost, directly impelling the worker’s human rights.The State, before this overview, no longer suffices to regulate labor rights, as labor relations go beyond its borders. At first comes the search for the regulation of labor rights in the International Labor Organization (ILO), however this organization, although extremely important, does not have enough structures to deal with the complexity of labor rights, due to its failure power of coercion and punishment. In order to reply to society, the International Labor Organization reproduces providing a right to freedom of association and collective bargaining as fundamental principles. Thus the suggested work aims to answer: How labor rights are being regulated in a global society facing the failure of the ILO? One of the solutions can be found in the structural coupling of labor law system and the economic system through International Treaties with the prediction of social clauses in a joint effort of the World Trade Organization and the International Labor Organization. In addition to this solution, and more effectively, there is the collective bargaining promoted by the unions and transactional companies. The Trade Unions are doing a constant effort in search of a worldwide regulation of social labor rights aiming to respect a worthy job to the worker. The provided theoretical support used is the Luhmann’s Theory of Social Systems. The method used is the deductive, because it will start from general premises to specific assumptions.
Keywords: Sociedade mundial; Direito laboral; Transnacionalização; Teoria sistêmica; Regulamentação; Organização internacional do trabalho; Organizações sindicais; World society; Labor law; Transnationality; Systemic theory; Regulation; International labor organization; Trade unions; ACCNPQ::Ciências Sociais Aplicadas::Direito